Error-Related Functional Connectivity of the Habenula in Humans - Li, Chiang-shan R. (Frontiers in Human Neuroscience, 2011)
Error detection is critical to the shaping of goal-oriented behavior. Recent studies in non-human primates delineated a circuit involving the lateral habenula (LH) and ventral tegmental area (VTA) in error detection. Neurons in the LH increased activity, preceding decreased activity in the VTA, to a missing reward, indicating a feedforward signal from the LH to VTA. In the current study we used connectivity analyses to reveal this pathway in humans. In 59 adults performing a stop signal task during functional magnetic resonance imaging (fMRI), we identified brain regions showing greater psychophysiological interaction with the habenula during stop error as compared to stop success trials. These regions included a cluster in the VTA/substantia nigra (SN), internal segment of globus pallidus (GPi), bilateral amygdala, and insula. Furthermore, using Granger causality and mediation analyses, we showed that the habenula Granger caused the VTA/SN, establishing the direction of this interaction, and that the habenula mediated the functional connectivity between the amgydala and VTA/SN during error processing. To our knowledge, these findings are the first to demonstrate a feedforward influence of the habenula on the VTA/SN during error detection in humans.